2020
DOI: 10.2196/19787
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Activity Trackers for Monitoring Adherence to Home Confinement During the COVID-19 Pandemic Worldwide: Data Aggregation and Analysis

Abstract: Background In the context of home confinement during the coronavirus disease (COVID-19) pandemic, objective, real-time data are needed to assess populations’ adherence to home confinement to adapt policies and control measures accordingly. Objective The aim of this study was to determine whether wearable activity trackers could provide information regarding users' adherence to home confinement policies because of their capacity for seamless and continuo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
102
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(120 citation statements)
references
References 5 publications
(5 reference statements)
15
102
0
Order By: Relevance
“…One worldwide study based on a smartphone app (Argus) showed that mean daily steps in different regions decreased by 5.5% and 27.3% (287 and 1432 steps/day, respectively) within 10 and 30 days after the COVID-19 pandemic was declared [ 10 ]. Another study that used a wristwatch with an embedded accelerometer (Withings) demonstrated a marked decrease in daily steps (from 25% to 54%) following the official dates of home confinement in countries adopting a total lockdown [ 11 ]. Similar findings were also reported in other countries [ 12 - 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…One worldwide study based on a smartphone app (Argus) showed that mean daily steps in different regions decreased by 5.5% and 27.3% (287 and 1432 steps/day, respectively) within 10 and 30 days after the COVID-19 pandemic was declared [ 10 ]. Another study that used a wristwatch with an embedded accelerometer (Withings) demonstrated a marked decrease in daily steps (from 25% to 54%) following the official dates of home confinement in countries adopting a total lockdown [ 11 ]. Similar findings were also reported in other countries [ 12 - 14 ].…”
Section: Discussionmentioning
confidence: 99%
“… 11 12 Currently, there is a lack of data on the relationship between PA and the effects of the COVID-19 pandemic. Limited data from PA trackers during lockdown 13 indicate that there has been a reduction in PA globally. However, few adolescents use PA trackers, 14 leaving large proportion of adolescents’ PA behaviours under-reported.…”
Section: Introductionmentioning
confidence: 99%
“…The measures of social distancing and “stay-at-home” messages, effective for controlling the pandemic, have directly affected these movement behaviors [ 11 ]. Quarantine measures reduce opportunities for physical activity, especially outdoor activities, and increase daily sedentary behaviors [ 12 ], which can affect cardiovascular [ 13 ], metabolic [ 14 ], and mental health [ 15 ]. However, although recent studies have shown the potentially harmful effects of physical inactivity and sedentary behaviors during the COVID-19 pandemic [ 16 , 17 ], less attention has been paid to the population groups that are clustering these unhealthy behaviors.…”
Section: Introductionmentioning
confidence: 99%